Low‐dose phase contrast mammography with conventional x‐ray sources. Issue 9 (7th August 2013) - Olivo, A.; Gkoumas, S.; Endrizzi, M.; Hagen, C. K.; Szafraniec, M. B.; Diemoz, P. C.; Munro, P. R. T.; Ignatyev, K.; Johnson, B.; Horrocks, J. A.; Vinnicombe, S. J.; Jones, J. L.; et al.
Abstract : Purpose: : To provide an x‐ray phase contrast imaging (XPCI) method working with conventional sources that could be readily translated into clinical practice. XPCI shows potential in synchrotron studies but attempts at translating it for use with conventional sources are subject to limitations in terms of field of view, stability, exposure time, and possibly most importantly, delivered dose. Methods: : Following the adaptation of our "edge‐illumination" XPCI technique for use with conventional x‐ray sources through the use of x‐ray masks, the authors have further modified the design of such masks to allow further reducing the dose delivered to the sample without affecting the phase sensitivity of the method. Results: : The authors have built a prototype based on the new mask design and used it to image ex vivo breast tissue samples containing malignant lesions. The authors compared images acquired with this prototype to those obtained with a conventional system. The authors demonstrate and quantify image improvements, especially in terms of microcalcification detection. On calcifications detected also by the conventional system, the authors measure contrast increases from five to nine fold; calcifications and other features were also detected which are completely invisible in the conventional image. Dose measurements confirmed that the above enhancements were achieved while delivering doses compatible with clinical practice. Conclusions: : The authors obtained phase‐related image enhancements in mammography by means of a system built with components available off‐the‐shelf that operates under exposure time and dose conditions compatible with clinical practice. This opens the way to a straightforward translation of phase enhanced imaging methods into clinical practice.